Egyptian Arabic-English Code-Switching Strategies of Colour Naming: Case Study of two Egyptian vlogs - Siereda, Natalia (Taikomoji kalbotyra, 2025)
This paper examines language choices between Egyptian Arabic and English in the use of colour terms within the bilingual online video performances of two Egyptian vloggers. The informants are two young Egyptian women whose YouTube content focuses on lifestyle topics, including shopping hauls and product reviews. In this case study, four hours of YouTube recordings were subjected to close qualitative analysis to explore how colour names and shades are expressed linguistically. Instances of colour naming in both English and Arabic were identified, and their frequencies were compared. Out of a total of 261 tokens, 52 were in English, 173 were in Arabic, and 36 were classified as mixed tokens. Using a usage-based approach, the study investigates the distribution of colour terms across languages and examines strategies of code-switching (CS). Particular attention is given to the use of basic colour terms (BCT), following Berlin and Kay’s (1969) theory. Finally, the linguistic choices of the two vloggers are compared to highlight similarities, differences, and potential patterns in their language use.